Endocrine management of children with Prader–Willi syndrome - Medeiros CB; Bordallo AP; Souza FM; Collett-Solberg PF (Dove Medical Press, 2013)
Clarice Borschiver Medeiros,1 Ana Paula Bordallo,1 Flavio Moutinho Souza,2 Paulo Ferrez Collett-Solberg1,31Endocrinology Unit, Departamento de Medicina Interna, Faculdade de Ciências Médicas, Universidade do Estado do Rio de Janeiro (UERJ), Rio de Janeiro, Brazil; 2Pediatric Endocrinology Unit, Departamento de Pediatria, Hospital Federal Cardoso Fontes – Ministério da Saúde do Brasil, Brasília, Brazil; 3Laboratório de Pesquisas Clínicas e Experimentais em Biologia Vascular (BioVasc), Universidade do Estado do Rio de Janeiro (UERJ), Rio de Janeiro, BrazilAbstract: Prader–Willi syndrome is a rare genetic condition afflicting nearly 1/15,000 live births. Clinical features include neonatal hypotonia, poor weight gain in early infancy followed by binge eating from childhood to adulthood, severe obesity, developmental delay, short stature, and hypogonadism of both central and peripheral etiology. Central hypothyroidism and adrenal insufficiency may occur. Sleep disordered breathing, by obstruction of upper airways associated with central hypoventilation, is a common feature. Most of these characteristics are assumed to be the result of a hypothalamic dysfunction. The most important complication and the most difficult to manage is the obesity. This review aims at discussing the most recent strategies to manage the endocrine complications of Prader–Willi syndrome patients, with a special approach on the treatment of obesity, hypogonadism, and short stature. We summarize the indication and effects of recombinant human growth hormone therapy on growth, cognitive development, and body composition, and discuss the effects of recombinant human growth hormone therapy on the resulting sleep disorders.Keywords: Prader–Willi syndrome, obesity, hypogonadism, growth hormone, sleep disorder